2014
DOI: 10.4028/www.scientific.net/kem.614.178
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Design and PCL-Substituting Systems of Total Knee Prosthesis

Abstract: Knee arthroplasty represents a laborious surgical procedure, involving a high degree of difficulty, concerning the bony tissue as well as soft tissues. Nevertheless, knee arthroplasty represents a procedure frequently used in orthopaedic clinics around the world, and its incidence it keeps growing [1].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Adam et al [6] compared various PCL-substitution implants in terms of the American Knee Society scores over 24 months. Kim et al [19] presented 68 monthfollow-up data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adam et al [6] compared various PCL-substitution implants in terms of the American Knee Society scores over 24 months. Kim et al [19] presented 68 monthfollow-up data.…”
Section: Discussionmentioning
confidence: 99%
“…[5] It is well-established that posterior cruciate ligament (PCL)-retaining and PCL-substitution prostheses are placed during total knee arthroplasty (TKA) in elderly with advanced gonarthrosis. [6] However, it remains unclear whether the implant design affects the balance and fall risks. One of the most controversial issues in TKA is whether to substitute or retain the PCL and it has been suggested that the choice is associated with risks of poor balance and falls postoperatively.…”
mentioning
confidence: 99%